A life cycle energy use and greenhouse gas emissions analysis of the corn stover feedstock supply system for cellulosic biorefineries. (26th April 2017) - Shah, Ajay; Darr, Matt
Abstract: Corn stover is the primary feedstock choice for most of the near‐term first‐generation cellulosic biorefineries in the Midwest with rated capacities between 76 and 114 million liters per year (MLPY). These biorefineries will require an annual feedstock supply of around 250–375 metric ton (t) to meet their feedstock demand. However, there is a dearth of studies based on sustainable ways to supply a vast quantity of feedstock to the biorefinery gate, thus this study focuses on stochastically evaluating the life‐cycle energy use and greenhouse gas emissions (GHGE) of the different components of corn stover based feedstock supply system of a 114 MLPY cellulosic biorefinery in the Midwest by using production‐scale experimental field data collected in Iowa. Different components of the supply chain considered includes corn stover harvesting in a large rectangular bale form, field collection, storage, handling and transportation. This study also evaluates the energy use and GHGE of nutrients removed from the field with collected stover. Average energy use, energy‐use ratio (EUR) and GHGE for this feedstock supply system of a Midwest‐based 114 MLPY biorefinery plant are estimated to be 1, 502 MJ std. t −1, 21%, and 95.2 kg‐CO2 e std. t −1, respectively. Nutrients removed during stover harvest shares 38 to 47% of the overall life‐cycle energy use and GHGE for the supply chain, followed by harvesting ( 24–28%) and transportation ( 23–27%). Life‐cycle GHGE and energy use are identified to be the most sensitive to the quantity of nitrogen removed, bale density, bale length, harvest rate, baler field efficiency and dry matter loss. © 2017 Society of Chemical Industry and John Wiley & Sons, Ltd